UiTM student wins first prize in MyTIGER Values Art competition 2025 - Jasmi, Muhammad Falihin (Universiti Teknologi MARA, 2025)
KUALA LUMPUR, 14 May 2025 – Muhammad Harith Zafran, a Bachelor of Landscape Architecture student from Universiti Teknologi MARA (UiTM) Puncak Alam, has emerged as the first prize winner in the Photo Imaging category of the MyTIGER Values Art Competition 2025, a national-level contest open to students from higher education institutions across Malaysia, organised by Maybank Foundation and Kakiseni. His thought-provoking artwork, titled REBORN, earned him a RM6,000 cash prize during the prize-giving ceremony held at Menara Maybank, officiated by Tan Sri Dato’ Sri Ir. Zamzamzairani Mohd Isa, Chairman of Maybank. Supervised by Mr. Muhammad Falihin Jasmi, a lecturer from UiTM Perak Branch, Harith’s winning piece was created in response to this year’s competition theme, which focused on Maybank’s TIGER core values and aligned with selected United Nations Sustainable Development Goals (SDGs)—namely SDG 13 (Climate Action), SDG 15 (Life on Land), and SDG 12 (Responsible Consumption and Production). REBORN is an artwork by Harith, inspired by the TIGER value of Growth and Surah An-Nur (24:45) from the Quran. The piece features a cracked egg, symbolizing life’s fragile beginnings. From this egg emerge animals, trees, and clouds, representing nature’s flourishing under divine guidance and human stewardship. Human hands cradling the egg emphasize humanity’s shared duty to nurture the environment. Through this visual metaphor, Harith highlights sustainable development, environmental awareness, and spiritual responsibility. REBORN conveys that true growth requires balance, care, and respect for all living beings, aligning with SDG principles of harmony between humanity and nature. The winning artwork will be showcased for public viewing at Balai Seni Maybank for one month, offering a platform for engagement with environmental, spiritual, and social themes through creative expression. This prestigious recognition affirms both Harith’s exceptional talent and UiTM’s dedication to cultivating visionary students who are prepared to address global challenges through innovation and art.